Association Between Enterovirus Infection and Asthma in Children: A 16-year Nationwide Population-based Cohort Study. Issue 9 (September 2018) - Wang, Ying-Ching; Tsai, Ching-Shu; Yang, Yao-Hsu; Huang, Kuo-You; Hsieh, Wen-Chi; Kuo, Ting-Yu; Chin-Hung Chen, Vincent; Wong, Jennifer; Ponton, Lynn; Wang, Tsu-Nai
Abstract : Background: Both virus-induced asthma and enterovirus (EV) infection are common in children; however, the relationship between EV infection and virus-induced asthma has not been systematically investigated in a cohort study. This nationwide population-based cohort study investigated the association between EV infection and asthma. Methods: We used data from the Taiwan National Health Insurance Research Database. The study sample consisted of insured children who were younger than 18 years and had EV infection between 1997 and 2013 and were followed until December 2013. We identified 36, 935 children with EV infection and compared them based on 36, 935 age-, sex-, urbanization- and income-matched controls to analyze the risk of subsequent asthma. Cox regression analyses were performed and adjusted for sex, age, urbanization, income, preterm labor and small for gestational age, perinatal complications, allergic rhinitis, allergic conjunctivitis, atopic dermatitis and bronchiolitis. Results: The mean follow-up interval for all patients was 8.59 years (standard deviation = 4.35 years). The mean latency period between initial EV infection and onset of asthma was 2.77 years (standard deviation = 2.43 years). EV infection was significantly associated with a higher incidence of asthma (hazard ratio = 1.65; 95% confidence interval: 1.60–1.71). Conclusions: A significant association was observed between EV infection and asthma in children. Health providers should be aware of the higher potential for children with EV to develop asthma in the future.